POLA USAHA MASYARAKAT NELAYAN DI DESA MAJAKERTA, KECAMATAN BALONGAN-KABUPATEN INDRAMAYU (Business Pattern of Fishermen in Majakerta Village, Balongan District-Indramayu Regency) - Nugroho, Thomas; Sulistiono, . (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2017)
ABSTRACTCapture fisheries business is a collective action in exploiting fisheries resources. It describes ability and dependency of community to capture fisheries resource that interestingly to be studied. The study was conducted for observing socio economic condition and analyzing small scale business of fishermen in Majakerta village Balongan Indramayu.  The survey method was used in this study, with purposive random sampling for collecting samples as many as 10 respondents. The results showed that a small scale business of fishing had an important role for fishermen community in Majakerta village.  Fishermen traditionally catch it, and they could be sustainable to do their business. It had financially profited with B / C ratio> 1.5 and payback period 1.5 dan payback period